Moral Reformation through the Sīrah: A Case Study of Ethical Implementation by Ḥaḍrat Mujaddid Alf e Thānī - Hasnain Ali,; Dr. Muhammad Arif Mateen, (Seerat Studies, 2025)
This paper explores the practical application of the Prophet Muḥammad’s (Peace be upon him) biography (Sīrah) as a foundational framework for integrated systems of education (Taʿlīm) and spiritual purification (Tazkiyyah). It argues that the Sīrah provides a holistic model that moves beyond mere historical narrative to offer a dynamic paradigm for human development, seamlessly merging the acquisition of knowledge with the cultivation of impeccable character (Iḥsān). The primary research objective is to derive core ethical principles from the Sīrah, such as compassion in mentorship and the primacy of action over speech, and to analyze their practical implementation, i.e., how these very principles were adopted, adapted, and propagated in the context of Sufism in the Subcontinent. This study narrows its focus to a specific case study: the contributions of Ḥaḍrat Mujaddid Alf e Thānī (d. 1624). It examines how he embedded the Prophetic ethical model into his teachings and reformist efforts. His methodology transformed his circle into a hub of learning that served not only as a theological seminary but also as a vibrant community for moral reformation and social upliftment, directly applying the Sīrah’s ethical lessons to the socio-religious context of Mughal India. Ultimately, through this historical analysis, this application positioned the Sīrah not as a historical artifact, but as a living, operative paradigm for spiritual and intellectual reform, as exemplified by the Mujaddid’s work. Keywords: Sīrah of the Prophet Muḥammad (Peace be upon him), Spiritual Purification, Sufism, Ethics, Prophetic Model, Mujaddid Alf-e-Thānī, Mughal India.